PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP PEMBELIAN KONSUMEN PADA IKKI BABY SPA - Qonita Dzatin Nuha; Syarif Thayib (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the influence of price and service quality on consumer purchasing decisions at Ikki Baby Spa Banyu Urip branch in Surabaya. The development of urban lifestyles has increased demand for baby and maternal care services, creating intense competition in the baby spa industry. The research method employed is quantitative with a causal associative approach. The research sample involved 112 respondents who are consumers of Ikki Baby Spa with the criteria of having used the service at least twice. The sampling technique used purposive sampling, while data analysis used multiple linear regression with SPSS version 25. The results showed that price has a positive and significant effect on purchasing decisions with a t-value of 9.463 and significance of 0.000. Service quality also has a positive and significant effect on purchasing decisions with a t-value of 6.294 and significance of 0.000. Simultaneously, price and service quality have a significant effect on purchasing decisions with an F-value of 64.508 and a coefficient of determination of 54.2%. These findings indicate that Ikki Baby Spa consumers highly consider the price aspect in decision-making, but still expect satisfactory service quality. This research provides managerial implications that companies need to maintain competitive pricing strategies while continuously improving service quality to strengthen market position.